O antropomorfizowaniu i potrzebie przedstawień figuralnych w sztuce greckiej - Bugaj, Ewa (Wydawnictwo Poznańskie, 2010)
At the beginning of the text ‘On anthropomorphising and the necessity for figural images in Greek art’, Ewa Bugaj notices that in the nomenclature related to Greek art, the term anthropomorphism was commonly accepted first of all in relation to anthropomorphising religious images – mainly deities. Therefore, it is inevitably connected with the idea of the cult image, difficult to define. Its contemporary understanding derives from the context outside the Greek world, principally linked with the criticism of idolatry. Nevertheless, the author claims that in ancient Greece there occurred one of the most typical forms of anthropomorphism, mostly explicit in the poems of Homer and Hesiod, where the attribution of human forms, customs, actions and characteristics to the gods is really paradigmatic, although there were some early philosophers who rejected and criticised such a way of perceiving the deity. Focusing first of all on the Greek phenomenon of anthropomorphising the deities, E. Bugaj reminds that throughout the period of development of the Greek ancient culture there existed various ways of depicting divinity, and that recognition of only one of them – expressed by anthropomorphised (human-like) images – is a great simplification. However, some historical premises suggest that also those deities that did not have a humanlike figure, exhibited human traits. On the margin of above considerations the author emphasises that the Greek phenomenon of anthropomorphising gods, who in Homer and Hesiod’s works expressed the whole assembly of human characteristics and vices, frequently unworthy of reproducing, does not testify to the lack of seriousness of religiousness of the Greeks, as shown by Walter Friedrich Otto and Walter Burkert. According to Burkert, depicting gods as non-heroic characters in the epic poetry, especially Homer’s, poetry that originated on the basis of the long and older oral tradition, is a long folk practice of narrating divinity. It fulfilled important functions of focusing attention and bringing the deity closer to people by showing them in ordinary, familiar situations. This tradition came to Greece from the Orient. The Greek religiousness is shown in the epic tales in a very serious and even severe way and it reveals a fear of gods, as it is not based on myths but first of all on practising cults, rituals comprising of scarifying victims, libations and praising gods. Next, Ewa Bugaj reflects upon cult images and their specifics, consisting in their necessity to present powers/beings transcendent for humans; they have to represent something without revealing the fact that this something (spiritual power, deity) is not visible on the basis of data from sensory experience, on the basis of direct observation. Referring to a number of scholars, the author explains that as far as the Greek world is concerned, all cult images were not to imitate any external model, which is basic for the modern understanding of an image (in Greece typical for conceptual thinking after Plato). Archaic Greek images of deities, especially the older ones, gave form to something that did not have it, albeit they did not imitate anything. The Greeks used a number of terms for the images, e.g. xoanon, bretas, andrias, palladion, agalma, kolossos, eikōn, eidōlon. What’s more, both terms and specific forms must have functioned together in ancient Greece and only confrontation of epigraphic and historic sources with archaeological data will demonstrate that looking for the explanation of these phenomena just in one category of sources, without its critical analysis, as well as using evolutionary schemes for the interpretation of the forms of the images is an unacceptable simplification. Giving examples from literature and art, E. Bugaj notices that bretas and xoana stood for non-iconic forms and they did not attempt to display any resemblance. They were imagined as something that falls down from the sky, such as xoanon of Athena Polias, located in Erechtheion on the Acropolis of Athens. However, such a deity ‘embodied’ in a non-iconic form could have been treated in various ways: it was carried in processions or ritually bathed, oiled and clothed (in the mentioned case from Acropolis in a specially woven peplos). Therefore, we witness here a specific form of anthropomorphism. Next, the author shows examples of preserved statues of the so called kouroi and korai – young boys and girls – from the archaic period, in order to demonstrate different ways of interpreting them – from cult statues to, at present most commonly accepted interpretation, emphasising their votive and commemorative function. Further, the author ponders upon the possibility of recognising other explanations of the fact that ancient Greeks created a culture, the most significant feature of which was common usage of images, frequently human-shaped. She refers primarily to works of Jean-Pierre Vernant and Alain Schnapp. E. Bugaj notices that the onset of immense popularity of visual images is dated from the so called geometric period, especially its end, when between the 9th and 8th century BC ancient Greece was an arena of fundamental changes. The religious system must have also undergone changes, taking the form of a state religion. On the one hand it expressed the uniqueness of particular Greek centres, and on the other, it endeavoured to confront various legendary traditions on a religious plan by the erection of common sanctuaries, organisation of Panhellenian Games and the panegiria. At the time in Greece, temples are for the first time constructed independently of human settings. They are inhabited by gods in anthropomorphic forms. What is more, this period witnessed the renovation of structures deserted for centuries, mostly grave structures, which began to serve as places of cult of legendary characters and heroes, not necessarily connected with them. Furthermore, their images are produced. Therefore, we may suppose that the development of figurative art in Greece with a central role of a human figure was first of all a significant means of communication for the society and of constructing its identity. In the sacral sphere it provided an opportunity for approaching a deity and contacting him/her through its anthropomorphised image. The author emphasises, however, that we should not talk about personal, individual or psychic relation with a god, because in the archaic epoch, as historic relations and studies within anthropology of culture prove, a man was not internally shaped as a separate individual personality. In Greece individuals existed only socially, as far as they were seen and people strived for approval in the eyes of their fellow citizens.
Estetyka w archeologii. Antropomorfizacje w pradziejach i starożytności, eds. E. Bugaj, A. P. Kowalski, Poznań: Wydawnictwo Poznańskie.
Keywords: ancient Greek Art and Archaeology; ancient Greek Culture and Religion